Cell Area-Based Method for Analyzing the Coverage Capacity of Satellite Constellations - Zhiming Song; Haidong Liu; Guangming Dai; Maocai Wang; Xiaoyu Chen (International Journal of Aerospace Engineering)
Constellation-to-ground coverage analysis is an important problem in practical satellite applications. The classical net point method is one of the most commonly used algorithms in resolving this problem, indicating that the computation efficiency significantly depends on the high-precision requirement. On this basis, an improved cell area-based method is proposed in this paper, in which a cell is used as the basic analytical unit. By calculating the accuracy area of a cell that is partly contained by the ground region or partly covered by the constellation, the accurate coverage area can be obtained accordingly. Experiments simulating different types of coverage problems are conducted, and the results reveal the correctness and high efficiency of the proposed analytical method.